Telling Lies, Telling Tales and Telling (and Doing) the Truth: Racism, Moral Repair and the Case for Reparations - Banner, Michael (Studies in Christian ethics, 2022)
First, in the section ‘Telling Lies’, this article attempts to illustrate recent everyday racism. Racism has a history and takes many different forms. I describe a particular practice of racism (found in Britain, circa 1970), which relied, for its doctrine, on supposedly scientific assumptions about biology and breeding—and received a confirming fillip through the celebration of monarchy, empire and rose-tinted history. Second, in ‘Telling Tales’, the story of Zacchaeus is taken as exemplifying a form of moral repair in which telling and doing the truth are intimately related. Third, in ‘Telling and Doing the Truth’, I contend that telling and doing the truth in relation to racism requires not only a clear naming of racism’s lies but also the making of reparations, for the reason that the lies of racism subtended manifold injustices, of which Atlantic slavery and the exploitation of colonies are notable instances. I take the history of the West Indies as providing a clear case where moral repair is (over)due, and I consider the form that reparations might take.